A review of latest clinical practice guidelines for the management of cancer-associated thrombosis. Issue 1 (March 2022) - Frere, Corinne; Wahl, Clementine; Rueda-Camino, Jose A.; Crichi, Benjamin; Prata, Pedro H.; Marjanovic, Zora; Farge, Dominique
Abstract: The management of cancer-associated thrombosis (CAT) poses unique challenges to healthcare professionals. While low‐molecular weight heparins (LMWHs) have long been the gold standard for both the primary and secondary prevention of CAT, results from large randomized controlled trials assessing the benefit of direct oral anticoagulants (DOACs) in both settings have resulted in some paradigm shifts. Herein, we review and compare recommendations from the latest authoritative clinical practice guidelines (CPGs) for the management of CAT and summarize the most recent evidence on available treatment options. A rigorous methodology was used to select high quality CPGs and compare the recommendations across CPGs. Only CPGs focusing on the management of CAT developed by a multidisciplinary international working group and issued or endorsed by national or international scientific societies, or government organizations were eligible for inclusion. The quality of selected CPGs was assessed using the Appraisal of Guidelines, Research, and Evaluation II (AGREE II) tool. Four CPGs met the inclusion criteria, including the International Initiative on Thrombosis and Cancer (ITAC), the American Society of Clinical Oncology (ASCO), the American Society of Hematology (ASH), and the National Comprehensive Cancer Network (NCCN).